2008
DOI: 10.1667/rr1263.1
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Neurogenesis and Neuroinflammation after Cranial Irradiation with56Fe Particles

Abstract: Exposure to heavy-ion radiation is considered a potential health risk in long-term space travel. In the central nervous system (CNS), loss of critical cellular components may lead to performance decrements that could ultimately compromise mission goals and long-term quality of life. Hippocampal-dependent cognitive impairments occur after exposure to ionizing radiation, and while the pathogenesis of this effect is not yet clear, it may involve the production of newly born neurons (neurogenesis) in the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 47 publications
2
95
2
Order By: Relevance
“…131 These observations have therefore triggered a number of cellular and molecular studies on neural cells and tissue, to gain understanding of the mechanisms of heavy ion-induced damage in the brain. These studies are ongoing, and despite some evidence of the involvement of reactive oxygen species (ROS) and neuroinflammation, 133 they are still preliminary and do not presently allow drawing a firm conclusion. fibroblasts were used in Han et al; 116 and HeLaxskin fibroblasts hybrid cells (CGL1) were studied in Elmore et al 117 On the contrary, we have now clear evidence that space radiation induces ocular cataract in astronauts, 134 and indeed lens opacification is the only proven space-radiation effects actually observed in crews of space missions.…”
Section: Late Effectsmentioning
confidence: 99%
“…131 These observations have therefore triggered a number of cellular and molecular studies on neural cells and tissue, to gain understanding of the mechanisms of heavy ion-induced damage in the brain. These studies are ongoing, and despite some evidence of the involvement of reactive oxygen species (ROS) and neuroinflammation, 133 they are still preliminary and do not presently allow drawing a firm conclusion. fibroblasts were used in Han et al; 116 and HeLaxskin fibroblasts hybrid cells (CGL1) were studied in Elmore et al 117 On the contrary, we have now clear evidence that space radiation induces ocular cataract in astronauts, 134 and indeed lens opacification is the only proven space-radiation effects actually observed in crews of space missions.…”
Section: Late Effectsmentioning
confidence: 99%
“…Sham-irradiated rats (n514) received the same procedure but without application of a cranial irradiation. Four collimators with a diameter of 3 cm each were used to place four rats and an ionization chamber simultaneously in the dose field for monitoring (PinPoint 0.016 cm 3 ; PTW, Freiburg, Germany). The lead shielding (7 cm thick) was used to limit radiation exposure to structures outside the brain, such as the eyes.…”
Section: Animals and Cranial Irradiationmentioning
confidence: 99%
“…1,2 Cranial irradiation of rodents shows that the long-term cognitive deficits are associated with impairment of hippocampal neurogenesis and an activation of microglia. [3][4][5][6] Due to the higher resistance of rodent brain to whole brain radiation, [7][8][9] most studies applied a high (8)(9)(10)(11)(12)(13)(14)(15) Gy) single dose. These experimental radiation protocols do not closely reflect the clinical situation, where WBRT is applied in smaller fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with low-LET radiation showed that radiation impairs not only proliferation of NPCs, but also persistently impairs their differentiation into neurons and other neural cells (Casadesus et al 2004(Casadesus et al , 2005Rola et al 2004aRola et al ,b, 2005Rola et al , 2008. NCRP Report 153 (NCRP 2006) notes that cells in the dentate subgranular zone (SGZ) undergo dose-dependent apoptosis and that the production of new neurons in young adult male mice is significantly reduced by relatively low (≤ 2 Gy) doses of X-rays.…”
Section: B Neurogenesismentioning
confidence: 99%